Is self-regulation key in reducing running-related injuries and chronic fatigue? A randomized controlled trial among long-distance runners. Issue 5 (3rd September 2022) - van Iperen, Luuk P.; de Jonge, Jan; Gevers, Josette M. P.; Vos, Steven B.; Hespanhol, Luiz
Abstract: Runners have a high risk of getting injured compared to practitioners of other sports, and reducing this risk appears challenging. A possible solution may lie in the self-regulatory behavior of runners and their passion for running, which are promising predictors of runners' risk of running-related injuries (RRIs) and chronic fatigue. Therefore, in the present study, we investigated to what extent a mobile application ("app"), called REMBO, could reduce the risk of RRIs and chronic fatigue by externally supporting self-regulation in a personalized fashion. Long-distance runners ( N = 425; 243 men, 182 women; M age = 44.7 years), training for half and whole marathon distances, took part in our randomized controlled trial. Runners were randomly allocated to theintervention group with access to the app ( n = 214) or to the control group with no access to the app ( n = 211). We tested the effectiveness of the app according to the intention-to-treat protocol and via a dose-response analysis, finding no statistically significant effects with regard to RRIs and chronic fatigue. Furthermore, an exploratory latent risk profile subgroup analysis found no evidence that any reductions in RRIs or chronic fatigue due to the app intervention differed across low-risk, medium-risk, and high-risk psychological profiles of runners. Across our study, adherence was relatively low, reasons for which are discussed based on feedback from participants. In our discussion, we outline the implications of the app intervention not achieving its intended effect and list several recommendations that might steer toward more success in preventing RRIs and chronic fatigue in the future.